ON THE QUESTION OF THE HELIUM ABUNDANCE IN ORION A MEASURED BY RADIO RECOMBINATION LINES. AND THE PRIMORDIAL HELIUM ABUNDANCE - Tsivilev, A. P. (Одеські астрономічні публікації, 2020)
Recombination radio lines (RRLs) of hydrogen (H), helium (He-4), and carbon (C) are a powerful tool for studying the interstellar medium (ISM) in space. The RRLs observations allow to obtain the physical parameters of regions of ionized hydrogen (HII regions) as well as of the photo-dissociation regions; and to estimate the effective temperature of stars that ionize the HII region. There is also an important cosmological task for RRL – measuring Primordial helium abundance produced at the stage of Primordial nucleosynthesis of the Universe. It turned out that the Orion A nebula is an interesting object for the latter task. At the time, the recombination radio lines observations of hydrogen, helium (H, He), and carbon (C) at a number of positions in the Orion A HII region were carry out with the RT22 radio telescope (Pushchino) at wavelengths of 8 and 13 mm. The relative helium abundance, y + = n(He + )/n(H + ), in these positions was obtained. The behavior of this value over the nebula showed that the helium ionization zone is smaller than the hydrogen one with different ratios for the core and halo. The location where the maximum y + value is expected was also determined. For the established ionization structure, it means that the actual helium abundance in Orion A, n(He)/n(H), will not be less than the maximum y + value. This allows to estimate the limitations on the Primordial helium abundance. In this work, new H and He RRL observations were made at 13 mm in the direction of the expected maximum of y + . RRLs were observed in two transitions - 65α and 66α. It was found that the maximum y + value is in the range of 10 − 12%. Hence, we can expect that the Primordial helium abundance (Yp, the ratio He/H by mass) lies in the range of ≈ 26.4 − 29%, and the number of light neutrino-type particles during Primordial nucleosynthesis may exceed the standard value. To refine the result the work will be continue.